Symbiotic Ideology in Historical Layering: Sustainable Development of Linhai City in Urbanisation - Yang, Yixuan (MAJ - Malaysia Architectural Journal, 2025)
The intensification of urbanisation poses new challenges to sustainable urban development. This paper firstly points out that the urban development of Linhai City, China, is characterised by a clear historical stratification in space, and then introduces the theory of symbiosis as a perspective for studying sustainable urban development. While using historical layering as a framework to connect time and space in order to study the use of symbiosis in the development of Linhai in different historical periods. The article will specifically analyse the cultural space, material space, and social space of Linhai’s ancient city area, old city area, Dayang new city, and Lingang new city, aiming to reveal the plurality and complexity of city’s development in the historical process. Its diverse urban layout not only adapts to the local conditions and respects the natural and historical heritage, but meets the needs of modern society, demonstrating the overall value and specific application of the concept of symbiosis in urban design. The article concludes by presenting the current problems of Linhai’s urban development and the guiding role of symbiosis ideology in solving the problems, which will provide a theoretical and practical reference for the sustainable development of Linhai and similar cities, as well as a new way of thinking for future research on sustainable development in China.